Correlation between religiosity and anxiety level in caregivers at intensive care unit - I Gusti Agung Ayu Yulianti; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani (Indoscholar Publication and the Indonesian Psychiatric Association, 2020)
Background: Patients admitted to the ICU are often in a state of uncertainty. This has an impact on the welfare of caregivers and other family members. This study aimed to determine the relationship between religiosity and the level of anxiety experienced by caregivers while accompanying patients in the ICU. Materials and Method: This study is a non-experimental observational cross-sectional study with analytic correlational design. The research sample was taken as many as 33 people as samples were carried out by consecutive sampling method. Results: Religiosity is negatively related to mild to moderate anxiety (R=-0.484, p >0.05). Religion is positively related to levels of moderate to severe anxiety (R=0.402, p=0.038). Conclusion: There is a negative relationship with the level of moderate strength between religiosity variables with mild to moderate levels of anxiety and there is a positive relationship between religiosity and moderate to very severe levels of anxiety in family caregiver ICU at Sanglah General Hospital in Denpasar.